STUDY OF PHARMACEUTICAL INVENTORY CONTROL SYSTEM IN SEVERAL PHARMACIES IN KARANGASEM, BALI - I Made Ari Anata; I Made Agus Gelgel Wirasuta (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2021)
The control of pharmaceutical products is one of the pharmaceutical services at the Pharmacy that is regulated in Permenkes RI No. 73 of 2016. The pharmacy control of each pharmacy must always apply the principles stated in the Good Pharmacy Practice (GPP) guidelines. GPP is a pharmaceutical practice that responds to the needs of people who use pharmacist services to provide optimal and evidence-based care. This study aims to determine the system of one of the pharmaceutical service standards, namely the control of pharmaceutical products in several pharmacies in Karangasem, Bali. This type of research is observational descriptive. Data retrieval is carried out in a retrospective manner related to the pharmaceutical product control system in the form of an order or procurement, dispensing, and handling system. Most pharmacies are researched to apply the same control system in the procurement and spending of pharmaceutical products. Only the pharmaceutical product system for handling parts has a slight difference in each pharmacy. Keywords: forensics; control; pharmaceutical products; pharmacies; pharmacists